Asymmetric Defluoroallylation of 4‐Trifluoromethylpyridines Enabled by Umpolung C−F Bond Activation. (21st March 2022) - Zhou, Fei‐Yu; Jiao, Lei
Abstract: Carbon–fluorine bond activation of the trifluoromethyl group represents an important approach to fluorine‐containing molecules. While selective defluorinative functionalization reactions of CF3 ‐containing substrates have been achieved by invoking difluorocarbocation, difluorocarboradical, or difluoroorganometallic species as the key intermediates, the transformations via fluorocarbanion mechanism only achieved limited success. Furthermore, the enantioselective defluorinative transformation of the CF3 group remained a formidable challenge. Here we report a defluorinative functionalization reaction of 4‐trifluoromethylpyridines involving difluoro(pyrid‐4‐yl)methyl anion as the key intermediate, which was developed based upon our previous studies on the N ‐boryl pyridyl anion chemistry. In particular, asymmetric defluoroallylation of 4‐trifluoromethylpyridines and ‐pyrimidines could be achieved by using Ir‐catalysis to forge a difluoroalkyl‐substituted chiral center. Abstract : Enantioselective defluorinative transformation of the trifluoromethyl group represents a formidable challenge. An asymmetric defluoroallylation reaction of 4‐trifluoromethylpyridines and ‐pyrimidines is reported, which features an umpolung C−F bond activation, a broad substrate scope and excellent enantioselectivities.